Copulas of Two-Dimensional Threshold Models - Haroutunian, Evgueni A.; Safaryan, Irina A. (Mathematical Problems of Computer Science, 2021)
A representation of two-dimensional random vector bivariate distribution by copula is proposed for the case when one of components is categorizing for the other. The regression function and the bounds for the Spearman rank correlation coefficient are derived.